Comparison of Convective Heat Transfer Coefficient and Friction Factor of TiO2 Nanofluid flow in a tube with Twisted Tape Inserts - Azmi, W. H.; Sharma, K. V.; Sarma, P. K.; R., Mamat; Shahrani, Anuar (Elsevier, 2014)
Nanofluids have gained extensive attention due to their role in improving the efficiency of thermal systems. The present study reports a further enhancement in heat transfer coefficients in combination with structural modifications of flow systems namely, the addition of tape inserts. Experiments are undertaken to determine heat transfer coefficients and friction factor of TiO2/water nanofluid up to 3.0% volume concentration at an average temperature of 30 C. The investigations are undertaken in the Reynolds number range of 8000-30,000 for flow in tubes and with tapes of different twist ratios. A significant enhancement of 23.2% in the heat transfer coefficients is observed at 1.0% concentration for flow in a tube. With the use of twisted tapes, the heat transfer coefficient increased with decrease in twist ratio for water and nanofluid. The heat transfer coefficient and friction factor are respectively 81.1% and 1.5 times greater at Re ¼ 23,558 with 1.0% concentration and twist ratio of 5, compared to values with flow of water in a tube. An increase in the nanofluid concentration to 3.0% decreased heat transfer coefficients to values lower than water for flow in a tube and with tape inserts. A thermal system with tape insert of twist ratio 15 and 1.0% TiO2 concentration gives maximum advantage ratio, if pressure drop is considered along with enhancement in heat transfer coefficient.